Pemberian Suplemen Branched Chain Amino Acids (BCAA) untuk Mengurangi Tingkat Kelelahan pada Mahasiswa Pendidikan Dokter Universitas Sebelas Maret - Abdulhamid, Muhammad; Kiyatno, .; Hikmayani, Nur Hafidha (Nexus Biomedika, 2013)
Background: Fatigue is a condition characterized by a decrease in work efficiency and endurance. BCAA capsule contains of three kinds of essential amino acids, those were leucine 2275 mg, isoleucine 1137.5 mg, and valine 1137.5 mg, each of which plays an important role in protein synthesis and energy system for activity. This study aimed to examine the effect of supplement administration of BCAA to reduce fatigue levels in medical students of Sebelas Maret University (UNS). Methods: This was an experimental research with pretest-posttest group design. It was conducted at Faculty of Medicine UNS on December 13th, 2012. Subjects (n=40) were randomly selected from list of current medical students at preclinical level. Subjects who had been fasting for eight hours, then, were randomly arranged into two groups: (1) control group whose fatigue levels were measured twice in resting condition at10-minute interval, and (2) treatment group whose fatigue levels were measured before and 10 minutes after BCAA administration. Fatigue referred to decreasing concentration determined by reaction time to light stimuli. Pretest-postest fatigue levels for each group were analyzed using paired sample t-tests, whereas posttest fatigue levels between the two groups were analyzed using independent sample t-test. Data analysis were performed using SPSS 17.0 for Windows. Results: Mean fatigue levels of control group at first and second measurement, each, were 270.1±15.3 and 255.5±10.9 millisecond. While mean fatigue levels of treatment group at pretest and after BCAA administration were 268.9 ± 14.8 and 211.7±38.8 millisecond, consecutively. Analysis of paired sample t test of pretest-postest fatique levels in both groups, each, showed significant difference (p = 0.001 for control group and p < 0.001 for treatment group), while analysis of independent t test of posttest fatigue levels between the two groups showed that the posttest fatigue levels between the two groups also differed significantly (p <0.001). Conclusions: BCAA administration significantly reduced fatigue levels in medical students of UNS. Fatigue levels were significantly shorter in subjects administered BCAA supplement than those of control group who did not take BCAA supplement. Keywords: BCAA suplement, fatigue